How does a change in risk perception affect the housing market - Evidence from an industrial accident in France - Marianne Bléhaut (European Regional Science Association (ERSA), 2014)
In 2001, the AZF plant exploded in Toulouse (France). The accident was unexpected, it strongly damaged local housing and benefited from a wide media coverage. It provides a rare opportunity to analyze the consequences of a shift in risk perception on housing markets and neighborhoods subject to industrial risk. Using a difference-in-difference matching strategy, this paper shows that although transaction prices do not change as a result of this shift, local housing markets are indeed affected. In particular, the vacancy rate increases, and the standard of living in the at-risk areas tends to deteriorate.
Keywords: R20; R21; R23; C21; 330